2012
DOI: 10.1186/1742-7622-9-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of improved rural sanitation on diarrhoea and helminth infection: design of a cluster-randomized trial in Orissa, India

Abstract: BackgroundInfectious diseases associated with poor sanitation such as diarrhoea, intestinal worms, trachoma and lymphatic filariasis continue to cause a large disease burden in low income settings and contribute substantially to child mortality and morbidity. Obtaining health impact data for rural sanitation campaigns poses a number of methodological challenges. Here we describe the design of a village-level cluster-randomised trial in the state of Orissa, India to evaluate the impact of an ongoing rural sanit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 35 publications
(44 reference statements)
0
49
0
Order By: Relevance
“…Hands can be contaminated by anal cleansing of oneself or a child that is not followed by handwashing with soap, and food can be contaminated during production or preparation. Animal faeces could also be contributing to the disease burden -a possibility that we are exploring in our sub-study of microbial source tracking (Clasen et al 2012). Exposure to rotavirus or zoonotic agents such as Cryptosporidium, both of which have been reported to be a major cause of moderateto-severe diarrhoea in India, might only be partly prevented by sanitation (Kotloff et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hands can be contaminated by anal cleansing of oneself or a child that is not followed by handwashing with soap, and food can be contaminated during production or preparation. Animal faeces could also be contributing to the disease burden -a possibility that we are exploring in our sub-study of microbial source tracking (Clasen et al 2012). Exposure to rotavirus or zoonotic agents such as Cryptosporidium, both of which have been reported to be a major cause of moderateto-severe diarrhoea in India, might only be partly prevented by sanitation (Kotloff et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Randomisation was stratified by administrative block to ensure an equal number of intervention and control villages in each block. Randomisation achieved a good balance of socio-economic and water-and sanitation-related characteristics (Clasen et al 2012). Masking of participants was not possible because of the nature of the intervention, but households were not told explicitly that the purpose of enrolment was to study the effect of a trial intervention, and the surveillance team was different from the intervention team.…”
Section: Randomisation and Maskingmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective cohort from rural Bangladesh enrolled in a pilot for this study found that children raised in households with improved sanitation, hygiene and water quality conditions had lower levels of parasite infection, better growth and improved EE biomarkers compared to children raised in households without such access 63. A trial to assess the impact of rural sanitation on diarrhoea includes length for age as a secondary outcome but is still underway 64. Taken together, the mixed evidence to date does not conclusively link improved WASH conditions with improved child growth and the field would benefit from additional efficacy studies.…”
Section: Introductionmentioning
confidence: 96%
“…11 Improper disposal of child feces is a potentially important vector for disease because of increased pathogen transmission from contact with sibling's feces, but it has received relatively little attention in the literature. 12 We developed a feces scooping tool intended to be easier to use than the common local practice of using a heavy garden hoe.…”
Section: Introductionmentioning
confidence: 99%